Social Media as a Tool for Fundraising: Analysing the Strategies of Indian Non-Profits During Covid-19 - Seema Sangra; Dr. Lokesh Sharma, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
This research examines the transformative role of social media in non-profit organisations' fundraising strategies during crises, focusing on Indian NGOs' digital adaptation during the COVID-19 pandemic. Through a detailed examination of two prominent Indian non-profits—The Akshaya Patra Foundation and Give India—this research employs content analysis and explanatory case study methods to analyze the effectiveness of social media in fundraising efforts. The study examines how these organizations adapted their digital communication strategies to engage stakeholders, raise awareness, and generate funds through crowd funding initiatives during the pandemic. The research methodology combines quantitative content analysis of social media campaigns with qualitative assessment of stakeholder engagement patterns to validate how social media content supports fundraising efforts during crisis periods. The findings reveal significant patterns in how successful non-profits leverage social media for crisis fundraising, demonstrating the crucial role of strategic digital communication in mobilizing resources for humanitarian causes. Based on these insights, the research proposes a comprehensive social model paradigm for non-profit organizations, providing practical frameworks for implementing effective social media campaign strategies. This study contributes to the growing body of knowledge on digital communication in the non-profit sector, offering valuable insights for organizations seeking to enhance their social media